Surgical treatment of right colon cancer - A. A. Nevolskikh; V. A. Avdeenko; I. P. Reznik; T. P. Pochuev; R. F. Zibirov; S. A. Ivanov; A. D. Kaprin (Сибирский онкологический журнал)
The study aimed to perform a systematic review of the literature on surgical treatment for right colon cancer (RCC) with complete mesocolic excision (CME) and D2/D3 lymph node dissection (LND). Material and Methods. A literature review was performed for studies published between 2013 and 2023 by the online resources from the official Web sites of the societies/panels and PubMed database. Sources included guidelines, meta-analyses, randomized and nonrandomized clinical studies, guidelines by European Society of Medical Oncology, the Japanese Society for Cancer of the Colon and Rectum, and the National Comprehensive Cancer Network, Russian clinical guidelines. Results. CME significantly improved both immediate and long-term treatment results, which was confirmed by numerous meta-analyses. The extent of LND remains one of the most controversial issues in RCC. For many Asian surgeons, D3 LND is the standard procedure for the treatment of RCC, whereas the European approach is more conservative and apical lymph node dissection is not mandatory. There are also large differences in understanding the extent of D3 LND in RCC. Most surgeons understand this term as dissection of adipose tissue along the anterior and lateral surface of the superior mesenteric vein, however, there are authors who perform circular dissection along the superior mesenteric vessels, considering this extent of surgery to be the most radical. Conclusion. It is necessary to standardize methods and effective criteria for quality control of CME for RCC and LND. In this case, external independent assessment of the quality of surgical intervention is important. There is also currently a growing number of studies in which intraoperative fluorescence imaging makes it possible to better visualize the location of the apical lymph nodes and individualize LND.